The impact of green marketing strategies on customer purchase decision in Zimbabwe's FMCG sector - Bake, Annie (Midlands State University, 2017)
The aim of the study was to find out if the adoption of green marketing strategies influences customer purchase decision process. In this study 36 Marketing managers, 32 Production managers and 118 customers from the FMCG sector were used as research subjects. A combination of quantitative and qualitative methods was used to gather and analyze data. The research instruments used were the questionnaire and interviews. The current trend of the world going green has prompted many manufacturers especially of Fast Moving Consumer Goods to shift their focus from conventional advertising, packaging and promotion of products to eco-advertising, eco-branding, eco-packaging and eco-labeling. To add to these changes, in Zimbabwe, the Environmental Management Agency has been advocating for the use of biodegradable packaging that does not damage the environment. This has seen many Fast Moving Consumer Goods manufacturers adopting green marketing strategies to try and avoid penalties and also to gain a competitive edge over other companies in the industry. The major findings were that many FMCG manufacturing companies are only adopting green marketing strategies to evade payment of penalties to the Environmental Management Agency and also to get a competitive edge over competitors. Many people are becoming environmentally conscious but still need educating on the green marketing and its strategies. Recommendations on how to implement successful green marketing strategies according to the findings of the study are proposed such as the importance of provision of knowledge to customers on green marketing issues. Further studies need to be done on green marketing strategies in other industries and the impact of green policies by the Government on the level of adoption by the consumers in others industries.